Analisis Model Pembelajaran Daring di Masa Pandemi Covid-19 - Kasidi Kasidi; Marhaeni Dwi Satyarini; Sri Widayati (Journal of Economic Education and Entrepreneurship, 2020)
Abstrak Penelitian ini dilatar belakangi oleh terjadinya wabah penyakit korona (covid-19) yang telah menjadi pandemik di seluruh dunia. Untuk mencegah terjadinya penularan penyakit tersebut, maka diberlakukan aturan untuk segala pekerjaan harus dilakukan dari rumah termasuk proses pembelajaran untuk seluruh jenjangTujuan penelitian ini adalah menemukan model-model pembelajaran daring yang dapat diterapkan selama masa pandemik covid-19. Responden dalam penelitian ini adalah mahasiswa Program Studi Pendidikan Ekonomi, Program Studi PPKn, dan Program Studi Bimbingan Konseling dengan jumlah mahasiswa 59 orang. Pengumpulan data dilakukan dengan questionner menggunakan aplikasi WhatsApp. Hasil penelitian menunjukkan bahwa: (1) model pembelajaran daring yang dapat digunakan dalam masa pandemik covid-19 diantaranya: aplikasi WhatsApp, e-mail, aplikasi laman dosen, aplikasi eLiv.ivet, aplikasi zoom meeting, aplikasi google classroom, aplikasi video call; (2) dari sisi prestasi akademik yang dicapai oleh para mahasiswa model pembelajaran daring cukup efektif, namun ditinjau dari segi biaya menjadi tidak efisien bagi mahasiswa, sementara itu efisien dicapai oleh mahasiswa ditinjau dari segi ruang dan waktu; (3) mahasiswa tidak mendapatkan pelayanan pembelajaran sebagaimana mestinya; (4) seratus persen responden dalam penelitian ini lebih senang dengan model pembelajaran tatap muka langsung. Kata Kunci: Analisis, Pembelajaran Daring, Masa Pandemi Covid-19 Abstract The title of this research is: Analysis of Online Learning Models during the Covid-19 Pandemic. The background for choosing this title is the learning process that originally could be carried out with a face-to-face model and is usually carried out in classrooms / laboratories with great force having to switch to online learning due to the outbreak of the corona disease (covid-19) which has become a pandemic all around the world. To prevent the spread of the disease, almost all countries in the world have imposed a rule that all work must be done from each foreigner's home, including the learning process from kindergarten to tertiary education. The objectives of this study to find a variety of online learning models that can be applied during the Covid-19 pandemics. Respondents in this study were students of the Economic Education Study Program, Civic Education, and Counseling Guidance Study Program with a total of 59 students. Data collection was carried out by sending questionnaires to respondents using the WhatsApp application. The results showed that: (1) online learning models that can be used during the Covid-19 pandemic include: the WhatsApp application, e-mail, the lecturer dashboard, the eLiv.ivet application, the zoom meeting application, the google classroom application, the video call application; (2) in terms of academic achievement achieved by students, the online learning model is quite effective, however in terms of cost it becomes inefficient for students, while it is efficient for students in terms of space and time; (3) students do not get learning services as they should; (4) one hundred percent of respondents in this study prefer face-to-face learning model. Keywords: Analysis, Online Learning, Covid-19 Pandemic Period